Assessment of Medical Service Pricing in China's Healthcare System: Challenges, Constraints, and Policy Recommendations - Xiong, Wenying; Deng, Yufan; Yang, Yili; Zhang, Yumeng; Pan, Jay (Frontiers in Public Health, 2021)
Medical service pricing reform was considered one of the focuses of China’s remarkable health reform. This paper preliminarily assessed the roles of medical service pricing under the context of China’s healthcare system. Specifically, we introduced the potential roles of medical service pricing in China, and pointed out relevant problems that emerged in practice as the result of reform-related activities. Multiple constraint factors that might have induced undesired outcomes were then recognized, namely the excessive diversity and specialization of medical services, the price inelasticity of patient’s demand, and the inadequate capability of both medical institutions and administrations. Finally, we provided policy recommendations to inform the ongoing medical service pricing reform in China from a long-term perspective.